Efficacy of the Molded Carbon Sorbent VNIITU-1 Used in Obstetric Practice - V. T. Dolgikh; L. G. Pyanova; S. V. Barinov; V. A. Likholobov; T. I. Dolgikh; E. I. Ryabchikova; D. V. Korneev (Общая реаниматология)
Objective: to develop a technology for obtaining the molded sorbent VNIITU1, to study its physicochemical and biomedical properties, and to evaluate its efficacy in preventing and treating pyoinflammatory complications in obstetrics.Materials and methods. The molded sorbent VNIITU-1 was designed from the carbon porous material based on nanodispersed carbon by mixing with a vehicle, extruding the mixture, drying the extrudate in an inert atmosphere, thermally treating and activating by steam, followed by washing with distilled water and drying (TU 9398043710698342013). The molded sorbent VNIITU-1 is apyrogenic and nontoxic (Toxicity Study Conclusion No. 1998.013.P dated 14.08.2013; Engineering Testing Assessment No. 12.404 ORTI/2013 dated 26.08.2013), it is destined for single administration, sterile, placed in a removable thread capron mesh container, and used to treat and prevent pyoseptic complications in puerperas at risk for infection, such as acute nonspecific postpartum endometritis. A total of 52 puerperas were examined and treated. They had been divided into 2 groups: a study group (n=37) and a comparison group (n=15). In the study group, the hemosorbent VNIITU1 as a porous carbon applicator was postpartum inserted into the uterine cavity, by concurrently performing traditional antibiotic therapy to prevent infectious complications. The comparison group received only traditional antibiotic therapy. The uterine cavity aspirate was examined for IL1β and IL6 levels, its microbial profile, and microbial growth patterns in culture media. The data were processed using a package of applied STATISTICA6.1 programs and standard mathematical tables in Microsoft Excel. Descriptive and variation statistical methods were applied. The data were presented as Me [low quartilehigh quartile (LQHQ)]; two pre and posttreatment dependent variables were compared using the Wilcoxon and Mann-Whitney tests.Results. The molded carbon sorbent VNIITU1 was found to have pronounced antibacterial activity against S.aureus, P.aeroginosa, K.pneumonia, E.coli and S.agalactiae. Examination of lavages from the surface of the sorbent after its removal from the uterine cavity, by using a transmission electron microscope, revealed castoff epithelial cells, leukocytes, macrophages, and microorganisms, which determines the capacity of the sorbent to eliminate not only soluble toxins, but also microorganisms and disintegrating cell elements. Conclusion. The proposed procedure to  postpartum endometritis in puer peras at risk for infection via insertion of the porous carbon applicator VNIITU1 into the uterine cavity is more effective than the traditional approach and it can improve treatment results, by completely eliminating pathogens from the uterus and by reducing the level of local proinflammatory cytokines.